Impaired Neurovascular Coupling in the APPxPS1 Mouse Model of Alzheimer's Disease - Rancillac, Armelle; Geoffroy, Helene; Rossier, Jean (Current Alzheimer Research, 2012)
The tight coupling between neuronal activity and the local increase of blood flow termed neurovascular coupling is essential for normal brain function. This mechanism of regulation is compromised in Alzheimer's Disease (AD). In order to determine whether a purely vascular dysfunction or a neuronal alteration of blood vessels diameter control could be responsible for the impaired neurovascular coupling observed in AD, blood vessels reactivity in response to different pharmacological stimulations was examined in double transgenic APPxPS1 mice model of AD. Blood vessels movements were monitored using infrared videomicroscopy ex vivo, in cortical slices of 8 month-old APPxPS1 and wild type (WT) mice. We quantified vasomotor responses induced either by direct blood vessel stimulation with a thromboxane A2 analogue, the U46619 (9,11-dideoxy-11a,9a-epoxymethanoprostaglandin F2α) or via the stimulation of interneurons with the nicotinic acetylcholine receptor (nAChRs) agonist DMPP (1,1-Dimethyl-4- phenylpiperazinium iodide). Using both types of stimulation, no significant differences were detected for the amplitude of blood vessel diameter changes between the transgenic APPxPS1 mice model of AD and WT mice, although the kinetics of recovery were slower in APPxPS1 mice. We find that activation of neocortical interneurons with DMPP induced both vasodilation via Nitric Oxide (NO) release and constriction via Neuropeptide Y (NPY) release. However, we observed a smaller proportion of reactive blood vessels following a neuronal activation in transgenic mice compared with WT mice. Altogether, these results suggest that in this mouse model of AD, deficiency in the cortical neurovascular coupling essentially results from a neuronal rather than a vascular dysfunction.
Keywords: neurovascular dysfunction